2023
DOI: 10.1109/jphot.2023.3234074
|View full text |Cite
|
Sign up to set email alerts
|

High-Q and FOM Dual-Band Polarization Dependent Ultra-Narrowband Terahertz Metamaterial Sensor

Abstract: Polarization-dependent dual-band THz metamaterial using a modified Trishul structure is proposed in this paper. The absorber has three layers namely, a conducting ground plane, a dielectric substrate, and a structure top metallic patch. The top and bottom metallic is made up of gold material and the dielectric substrate is polyimide. The characteristics are obtained using the finite element method. The structure has obtained two resonant peaks at 0.78 THz(f1) and 1.65 THz(f2) for the X-polarized wave and at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Therefore, triple absorption bands are obtained due to the multiple resonators with different shapes and size [34]. Further, our proposed sensor is different from that reported in [9,11] in design geometry and performance. The suggested design has a larger sensitivity than 1649.8 GHz/RIU presented by Azab et al, [9] that is based on octagonal two concentric rings.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Therefore, triple absorption bands are obtained due to the multiple resonators with different shapes and size [34]. Further, our proposed sensor is different from that reported in [9,11] in design geometry and performance. The suggested design has a larger sensitivity than 1649.8 GHz/RIU presented by Azab et al, [9] that is based on octagonal two concentric rings.…”
Section: Introductionmentioning
confidence: 68%
“…It is revealed that the suggested sensor achieves larger sensitivity than those reported in the literature. In addition, the reported sensor has the highest quality factor, but the quality factor is lower than that presented in [11], [65], [67], [71]. In [11], the authors have suggested a high-quality factor sensor but with very low sensitivity and figure of merit.…”
Section: (B)mentioning
confidence: 86%
See 3 more Smart Citations